Shaping Virtual Religious Authority: The Power of Digital Media on Micro-Celebrity Da’i - Baidawi, Baidawi (JAWAB: Journal of Asian World and Islamic Behavior Journal of Asian World and Islamic Behavior, 2025)
Micro-celebrities preachers have taken an important part in educating the ummah through Islamic messages while establishing virtual religious authority. Celeb da’i gain strategic space and recognition from the community through religious studies and have the potential to become a reference for religious knowledge. The contestation of virtual religious authority with traditional religious authority as an authoritative source is dynamic, and at the same time fragmentation occurs. This research concentrates on da’i micro-celebrities including Ustadzah Oki Setiana Dewi, Ustad Syam, and Aa Gym. This research is focused on three digital platforms including YouTube, TikTok and Instagram. The time span of this research starts from February to July 2024. The research method uses descriptive qualitative through netnography studies. The finding is that virtual religious authority is illustrated through the digital platform micro-celebrities da’i, which offers a new face of entertainment, adapts to the latest trends, and is solutive in carrying out religious missions. The power of digital media catapults the popularity and religious influence of celeb da’i in the Islamic cyber environment, further perpetuating virtual religious authority as a source of religious information for the ummah.